Persepsi Pengajar dan Pemelajar terhadap Penggunaan Teknologi dalam Pengajaran Bahasa Inggris - Rita Karmila Sari (Universitas Indraprasta PGRI Jakarta, 2017)
Although Indonesian Government has established a policy on the necessity of integrating Information and Communication Technology (ICT) into school teaching to enhance the quality of education, there is still a concern that ICT utilization is not as mandated by the government. This study investigates the use of ICT in English teaching based on the perceptions of teachers and students in International-Standard School Pilot Project (RSBI). The data collected through questionnaires, observations and interviews in three High Schools and three Vocational Schools with RSBI certification in Padang are from the first semester of 2011/2012. The result shows the application of ICT in teaching English is only to access information and not to communicate. Also, the lack of supporting infrastructure is still the main barrier to the use of ICT in English teaching. Nevertheless, teachers and students agree that ICT is very useful for teaching English. Besides, this study finds the implementation of blended learning in Vocational Schools through an online, government-funded learning program DynEd.